THE REALITY OF SUSTAINABLE DEVELOPMENT IN DEVELOPING COUNTRIES AND THE PROSPECTS FOR ACHIEVING IT IN 2030 - Eman Alzubaidi (Mesopotamia Journal of Agriculture)
The research aims to conduct a standard economic analysis of the most important economic indicators related to sustainable development affecting the GDP of the sample countries (Iraq, Egypt, Jordan), Based on the premise that despite the vigorous pursuit of sustainable development, developing countries remain below the required level through the reduction of many indicators of sustainable development and the challenges facing sample States, The research relied on the descriptive and analytical approach using the Eviews10 programmer using time chains and two periods before forecast (2015-2022) and for forecasting (2023-2030). The data were divided into quarterly views to increase the number of views and to see the impact of some economic indicators of sustainable development on the adopted variable of sample States' GDP, The researcher concluded that sustainable development is not the level required and desired from it between (2015-2022) and that the variables got worse during the prediction that the sample states did not pay this great attention. The researcher recommended paying attention to the economic aspect, which is central to the dimensions and indicators of sustainable development, focusing on the environmental, technological, and social aspects as well, focusing on the establishment of financial funds to support sustainable development programs, and supporting research, media and cultural projects towards the establishment of environmentally friendly and beneficial projects for poor classes.